2009
DOI: 10.1055/s-0037-1621492
|View full text |Cite
|
Sign up to set email alerts
|

No differences in support of thrombin generation by neonatal or adult platelets

Abstract: Our results do not provide any evidence that a different PL content or expression of neonatal platelets may alter TG in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…

Phosphatidylserine (PS) exposure: Annexin V, which binds PS with high affinity, can be used to characterize the procoagulant phenotype of activated platelets. Analysis of PS exposure through measurement of Annexin V binding via flow cytometry has shown that the procoagulant phenotype is similar for both cord blood-derived platelets and adult platelets following stimulation with thrombin (17,18). Along these lines, phospholipid content of adult and cord blood platelets has also been reported to be similar (17,18).

…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…

Phosphatidylserine (PS) exposure: Annexin V, which binds PS with high affinity, can be used to characterize the procoagulant phenotype of activated platelets. Analysis of PS exposure through measurement of Annexin V binding via flow cytometry has shown that the procoagulant phenotype is similar for both cord blood-derived platelets and adult platelets following stimulation with thrombin (17,18). Along these lines, phospholipid content of adult and cord blood platelets has also been reported to be similar (17,18).

…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of PS exposure through measurement of Annexin V binding via flow cytometry has shown that the procoagulant phenotype is similar for both cord blood-derived platelets and adult platelets following stimulation with thrombin (17,18). Along these lines, phospholipid content of adult and cord blood platelets has also been reported to be similar (17,18). The procoagulant phenotype of peripheral blood-derived neonatal platelets has yet to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the venoms used in this study and their dependence on endogenous phospholipids for their coagulotoxicity, our previous work showed that D. russelii venom is unusually highly dependent upon phospholipid for the activation of Factor X [ 49 ], which is not mirrored by species within the genera Macrovipera , Oxyuranus , or Pseudonaja [ 49 , 67 ]. However, no differences in phospholipid levels have been observed between paediatric and adult plasma [ 68 ], suggesting that phospholipid levels do not explain the differential potency of D. russelii venom upon the two plasmas. The observed difference may therefore be related to the mechanism of procoagulant action and requires future work to elucidate.…”
Section: Resultsmentioning
confidence: 99%
“…The phospholipid content and baseline exposure of platelet surface phosphatidylserine is comparable in adults and newborns [65,66]. However, more platelet microparticles are generated and more phosphatidylserine molecules are exposed in the term and preterm platelets when thrombin or calcium ionophores were used as activators [67].…”
Section: Newborn Plateletsmentioning
confidence: 99%